Ireland's New National Planning Framework: (Re)Balancing and (Re)Conceiving Planning for the Twenty-First Century?. (20th October 2018) - Lennon, Mick; Scott, Mark; Russell, Paula
ABSTRACT: This article examines the recent evolution of national spatial planning in Ireland, focusing on the recent publication of National Planning Framework (NPF) in 2018. The NPF is Ireland's second national strategy for spatial development and represents a further shift away from traditional land-use regulation towards broader-based strategic spatial planning. In this commentary, we reflect on official perspectives regarding the role that planning should perform in a period of significant social, economic and environmental change and how planning policy conceives of 'balance' between competing priorities in the 'public interest'. We contend that this 'balance' is weighted heavily towards development enablement.